Demarcation of marine lands: historical aspects (PerCursos, 2025)
The demarcation of marine lands for the correct definition of the limits between the Union's property and its borders has always generated uncertainty, both due to the legal definition and the method of measurement and demarcation. This article discusses the regulations and legislation applied directly to the determination of navies throughout history, showing how the characterization of this range has been changed without presenting an enforceable rule. To this end, bibliographical research was carried out in legislation and regulations, as well as in academic publications, seeking to understand how the main elements that defined the navy line and the main controversies related to the topic emerged. As results, several methods used and intended to materialize erroneous legislation are presented, which only allowed a disorderly occupation of this area. As a result, after more than quarters of years, the country still did not have a territorial registry with correctly identified limits.
Keywords: marine land; demarcation; tide; legislation; SPU